A retrospective and observational study of urological anomalies in anorectal malformation in children at a tertiary care center in Telangana - Srinivas Srirampur; Kavimozhy Ilakkiya Poyyamozhy; Kumbha, Nagarjuna (Asian Journal of Medical Sciences, 2023)
Background: Anorectal malformations (ARM) are one of the common congenital abnormalities in a pediatric surgical unit. Urological anomalies occur frequently with ARM and the incidence increases with increasing complexity of ARM having dramatic impact on quality of life. Aims and Objectives: This study is done with an objective to know the incidence of various urological anomalies in ARM and comparing our observation with existing literature. Materials and Methods: This is a retrospective study conducted in Pediatric Surgical unit, Gandhi Medical College and Hospital, Secunderabad, from January 2017 to December 2021 based on the records of 45 patients who were diagnosed to have ARM with urological anomalies. Incidence of urological anomalies in ARM is studied with respect to demographic data and pattern of coexistence. Results: Total number of ARM cases noted during the period of study was 101, of which 45 cases had associated urological anomalies and these 45 cases were taken in this study. The overall incidence of urological anomalies was 42.5%. The incidence of urological anomalies was significantly swelled up in high ARM when compared with low lesion. Vesicoureteric reflux and hydroureteronephrosis were the most common anomalies observed in our study. Conclusion: The high incidence of associated urological anomalies necessitates standardized protocol of investigating all ARM patients as it is an important cause of morbidity and mortality. Early diagnosis warrants timely intervention and prevents upper urinary tract deterioration.